Psychosocial Adjustment Versus Vulnerability Profiles in Spanish Adolescents - Pastor, Yolanda (Revista de Psicología, 2016)
The aim of this paper was to describe profiles of psychosocial adjustment and vulnerability in adolescents, and to study its relationship with emotional distress in a representative sample of young people (52% boys and 48% girls) between 11 and 16 years old (M = 13.38; SD = 1.70) from Elche city (Alicante, Spain). The variables considered for the profiles’ construction were: gender, academic level, self-concept dimen-sions, self-esteem, perceived social support, family cohesion, school adaptation, community feeling, hostile cognitions and behavior problems. A Two-step Clustering Procedure was used and additional variance and discriminant analyses were performed to contribute to the statistical robustness of the results, which revealed four groups of adolescents ranging from higher to lower psychosocial adjustment. Indicators of emotional distress contributed to discriminate between groups, so that groups with higher psychosocial vulnerability showed higher emotional problems. This paper offers recommendations for the detection of adolescents in psychosocial risk, as well as for the prevention and design of programmes.